Future perspectives of extreme events and water availability in Brazilian catchments - Ballarin, André Simões (2024)
Global warming is projected to alter the frequency and magnitude of extreme events, posing major challenges to water resources worldwide. Understanding how these changes are projected to occur is paramount to tackle water scarcity-related experiences by guiding policymakers on developing local-to-regional adaptation plans. The present thesis has as its primary goal to investigate the projected impacts of climate change on extreme events and water availability in Brazilian catchments. To this end, we first present, in Chapter 2, the CLIMBra dataset, which comprises bias-corrected CMIP6 historical and future simulations for different climate variables for the Brazilian territory. These projections provide valuable insights into future climate scenarios and are the cornerstone for the development of the present thesis. By using the developed dataset, we further assessed how rainfall events of different magnitudes are projected to change across Brazilian catchments in Chapter 3. Our results indicated a widespread intensification of extreme rainfall events throughout the country, mainly dictated by changes in frequency, rather than intensity. Such projected changes in rainfall events, added to an expected increase in atmospheric water demand, are also expected to affect meteorological droughts across the Brazilian territory. As we show in Chapter 4, most of the evaluated Brazilian catchments are expected to experience longer, more intense, and frequent droughts in the future, with high CMIP6-model agreement. Beyond assessing projected changes of future drought events, we discussed in this chapter droughts\' occurrence under both land use and water demand perspectives and propose a new framework to better understand their link with changes in long- and short-term conditions of precipitation and potential evapotranspiration. Finally, in Chapter 5, we propose a Budyko-based framework for assessing future water availability and security scenarios across Brazilian catchments, considering both climatic and anthropogenic factors. The study revealed that most catchments are expected to exhibit a worse water security condition by the end of the century, driven primarily by enhanced human water use. We believe the present thesis contributes to advancing the current understanding of climate variability and its impacts on hydrological processes and water resources management in Brazil. By providing insights into future climate change scenarios of extreme rainfall events, meteorological drought, and water availability, this research might be valuable to inform decision-making processes aimed at enhancing Brazilian water resilience in the face of global warming.